Taxes and society's priorities - Bissinger, Caleb (Introducing issues with opposing viewpoints., 2018)
Presents a collection of fourteen opposing essays related to taxes and their role in society. Discusses why taxes are required, whether taxes are practical or moral, and tax reform. Includes facts and statistics, organizations to contact, and further resources.